Evaluation of Udaipur Rock Phosphate as Phosphorus Fertilizer in Soybean (Glycine max L. Merrill) Grown on Acid Upland Soils of Nagaland - Engrala Ao and R.C. Gupta, I. Jaleel Basha, A. K. Singh (Journal of the Indian Society of Soil Science, 2018)
Phosphorus (P) is one of the limiting nutrients in most of the soils due to its low solubility and highfixation. Low-grade Udaipur rock phosphate (URP) was evaluated as source of P to soybean (Glycine maxL. Merrill). The study revealed that Bray’s P increased significantly over 15 days of incubation, and theincrease was observed up to 90 days. No definite change was observed in the pH of soil. The lowest pHwas recorded with phosphate solubilizing microorganism (PSM) followed by partially acidulated URP(PAURP) + FYM. In the field experiment, the yield and yield attributes of soybean showed significantresponse to different treatments. Likewise, P uptake and P use efficiency (PUE) were highest under PAURP+ FYM. The organic carbon content was not significantly affected by P sources with or without FYM andPSM. However, the treatment effect was significant for available N, P and K, with highest under PAURP +FYM. It can be concluded that the application of PAURP @ 60 kg P2O5 along with FYM @ 5 t ha-1 is mosteffective to increase the yield and quality of soybean and residual soil nutrient status under acidic soilcondition of Nagaland. Also, the application of PAURP is a better alternative to the conventional Pfertilizersto minimize the cost.